Desenvolvimento de metodologia analítica para a determinação de adulterantes em café por termogravimetria e quimiometria - Pereira, Lucas Henrico (2019)
Brazil is the country with largest production and export of coffee beans, being a globally consumed product with high economic values. This way may be tampered with in a fraudulent or accidental manner. Fraudulent tampering is characterized by the use of cheaper products that are difficult for consumers to detect. The main adulterants that can be found in the coffee mix are corn, rye, rice, barley, wheat and also husks and straw for the coffee benefit, due to the low economic cost, some similarity with coffee and the high availability. Several techniques are already used for the detection of such adulterants, as well as infrared spectroscopy, electron microscopy, high performance liquid chromatography. Among the most used thermal analysis is the differential scanning calorimetry. Therefore, the present work aimed to determine the adulteration in coffee samples by thermogravimetric analysis technique, associated with chemometric methods. Thermogravimetric (TG) analysis is a technique in which determine mass loss or mass gain or mass percentage as a function of temperature or time. The samples were prepared in various mixtures containing the main contaminants such different proportions (1%, 2%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 50%) (w / w) with coffee powder. The thermal degradation studies of these materials were performed in TG, to perform the analyzes the atmospheres employed were in nitrogen and synthetic air. To quantify the level of tampering, PLS (Partial Least Squares) models were built using the Matlab software. Results of calibration errors for nitrogen gas atmosphere (corn 2.34; husk 3.91; straw 3.57), prediction errors (corn 2.63; husk 1.40; straw 7.70), latent variables (corn 4; husk 3; straw 4) and calibration errors for synthetic air atmosphere (corn 2.54; husk 3.56; straw 2.66), latent variables (corn 4; husk 5; straw 4) with the application of chemometric models, it was possible to confirm the previous results obtained by the technique, thermogravimetry and thus the PLS chemometric tool is promising for the study of adulteration in adulterated coffee samples